EDUCATION IN CONFLICT: POSTWAR SCHOOL BUILDINGS OF CYPRUS - Aydinlik, Sevil; Pulhan, Hifsiye (Open House Int, 2019)
The terms Cyprus, conflict, crisis and war have been almost inextricably intertwined throughout the history of this Mediterranean island. The education system played an important role socially and school buildings played an important role visually first in the dissemination of nationalism when the ethno-nationalist movements within the Turkish and Greek-Cypriot communities increased dramatically under British colonial rule (1878-1960), and later in the dissemination of internationalism in the mid-twentieth century. Despite the increased conflict and nationalism, which was reflected by Neo-Greek architectural elements, the striking impact of the International Style turned school buildings into representations of the communities' attitudes towards modernism. By the mid-1940s these attitudes towards modernism also served as a latent way for communities' identity struggles and for the sovereignty of each community to exist. After World War II the style embodied by many school buildings conveyed science-based modern thought; modernization attempts for political, economic and social reforms; and the strong commitment of the first modernist Cypriot architects to the spirit of the time and the philosophy of the modern. Under this scope, postwar school buildings in Cyprus are identified as unique artifacts transformed from an 'ethnicity-based' image into an 'environment-based' form that is more associated with the modernization, decolonization and nation-building processes from which local nuances of mainstream modernism emerged. At this point the modernization process of the state, identity struggles of the communities and architects' modernist attempts could be interpreted as providing a fertile ground for new social and architectural experiments, and could answer questions about how postwar school architecture managed to avoid reference to historical, ethnic and religious identities when there was an intentional exacerbation of hostility between the two ethnic communities and about school buildings predominantly followed principles of the International Style even though both the Greek and Turkish-Cypriot education systems were instrumental in strengthening local nationalisms and even ethnic tensions.
Keywords: Conflict; School Buildings; Nationalism; Modernism; Cyprus